2014
DOI: 10.1292/jvms.14-0260
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exposure to Male Goat Hair Extracts on Luteinizing Hormone Secretion and Neuronal Activation in Seasonally Anestrous Ewes

Abstract: In sheep and goats, exposure of seasonally anestrous females to males or their fleece/hair activates the gonadotropin-releasing hormone (GnRH) pulse generator leading to pulsatile luteinizing hormone (LH) secretion. Pheromones emitted by sexually mature males are thought to play a prominent role in this male effect. In the present study, we first aimed to clarify whether the male goat pheromone is effective in ewes. Seasonally anestrous St. Croix ewes were exposed to hair extracts derived from either intact or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…In temperate zones, climatic changes occur concomitantly with changes in seasons, and environmental factors such as temperature, day length and food supply are drastically altered. Some animals, such as hamsters (Weems, Goodman, & Lehman, 2015), deer (Barrell et al, 2016), buffalo (de Carvalho, Soares, & Baruselli, 2016), goats and sheep (Ohara et al, 2014), prefer to give birth in warm and food abundant seasons. Consequently, they exhibit physiological seasonal regulation in step with the changing seasons, known as seasonal reproduction.…”
Section: Introductionmentioning
confidence: 99%
“…In temperate zones, climatic changes occur concomitantly with changes in seasons, and environmental factors such as temperature, day length and food supply are drastically altered. Some animals, such as hamsters (Weems, Goodman, & Lehman, 2015), deer (Barrell et al, 2016), buffalo (de Carvalho, Soares, & Baruselli, 2016), goats and sheep (Ohara et al, 2014), prefer to give birth in warm and food abundant seasons. Consequently, they exhibit physiological seasonal regulation in step with the changing seasons, known as seasonal reproduction.…”
Section: Introductionmentioning
confidence: 99%
“…In the accessory olfactory bulb on the other hand while Fos expression was higher after exposure to male odor than after the control situation it showed a similar response to female odor, indicating that the accessory olfactory system may respond more generally to social odors rather than in selective detection of those associated with males. These results are however challenged by a recent study which found Fos activation in the accessory but not the main olfactory system of St Croix ewes in response to extracts of hair from male goats that induce an increase in LH secretion (Ohara et al, 2014 ). However, the physiological relevance of these intriguing results remains to be established.…”
Section: Neural Circuitry Involved In the Ram Effectmentioning
confidence: 87%
“…The olfactory stimuli which generate the “ram effect” are not strictly species specific since hair from male goats stimulates LH pulsatile secretion (Over et al, 1990 ) and induces ovulation in ewes (Birch et al, 1989 ). A recent study showed that an acidic fraction of male goat hair that stimulated multiunit activity of the mediobasal hypothalamus of ovariectomized Shiba goats also stimulated pulsatile LH secretion in St Croix ewes (Ohara et al, 2014 ). The same group has also used this approach to show that 4-ethyloctanol is of key importance for activating the GnRH pulse generator in goats (Murata et al, 2014 ).…”
Section: The Stimuli Involvedmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, exposing females to the odour of the male (wool, hair) strongly stimulates LH pulsatility in both sheep and goat (4,5) and therefore, the effect of the ram or the buck on the LH secretion of females can be mimicked by presentation of their odours (6,7). According to the definition of Karlson and Lüscher (8), ram and buck odours could thus be classified as primer pheromones, but several authors reported that goat "pheromones" could induce LH secretion in anoestrus ewes (9,10). This apparent lack of specificity is clearly not in favour of a pheromonal action.…”
Section: Introductionmentioning
confidence: 99%